Cirrhilabrus cyanogularis, a new species of fairy wrasse from the Philippines and Indonesia (Teleostei: Labridae) - Tea, Yi-Kai; Frable, Benjamin W.; Gill, Anthony C. (Zootaxa, 2018)
Cirrhilabrus cyanogularis, sp. nov., is described on the basis of the holotype and three paratypes from Banguingui Island, Sulu Archipelago, Philippines, and a paratype from Sulawesi, Indonesia. The new species belongs to a complex consisting of C. filamentosus (Klausewitz), C. rubripinnis Randall & Carpenter, and C. tonozukai Allen & Kuiter. Aside from similar nuptial male coloration, the four species share the following character combination: a single row of cheek scales; dorsal-fin spines taller than dorsal-fin rays (slightly incised between spinuous and soft dorsal fin in C. rubripinnis and C. cyanogularis; last three dorsal-fin spines converging to form a single filament in C. tonozukai and C. filamentosus); relatively long pelvic fins (reaching past anal-fin origin); and isthmus and breast blue. The new species differs from the other members of the complex in lacking a dorsal filament, as well as possessing six predorsal scales, more extensive blue coloration on the isthmus, lower head and breast, and a soft dorsal fin with narrow black, medial stripe. The status of Klausewitz’s Cirrhilabrichthys is briefly discussed.